(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
The process of teaching piano in junior groups of the academic class requires not only the development of technical skills but also the cultivation of artistic and creative abilities. This article examines the main pedagogical methods that contribute to the formation of expressive and imaginative performance in young pianists, integrating technical mastery with artistic interpretation.